Correction: "Timely help" or "one disaster after another": The impact of potential and transition interim CEO succession on corporate performance. - Conghui Zhao; Xin Guan; Xinyue Wu (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0311281.].